Pharmacoepidemiology day 2023: a fun and interactive way to understand pharmacoepidemiology / Zakiah Mohd Noordin and Dr. Mahmathi Karuppannan - Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Pharmacoepidemiology and Public Health course is offered to second year pharmacy students in their 2nd semester. The course introduces students to different types of pharmacoepidemiology study designs. Pertaining to that, Pharmacoepidemiology day was organised as one of the assessments. The assessment aims to enhance student's ability to describe the mainconcepts, in pharmacoepidemiology demonstrate problem solving skills in social and cultural aspects of pharmacy practice and display information management skills in drug information and literature evaluation. All Faculty of Pharmacy staff and students were invited to participate in the program.